Academic Quality Acceleration: An Evaluation of Digital System and Information Quality - Jaya Roza Azzukhrufi; Fitriana Fitriana; Andi Kristanto; Syunu Trihantoyo (Management of Education: Jurnal Manajemen Pendidikan Islam, 2026)
Academic information systems are now central to university administration, but their contribution to academic quality depends on more than technical performance. Drawing on the DeLone and McLean Information Systems Success Model, this study examined how System Quality and Information Quality were associated with Academic Quality Acceleration. Survey data were obtained from 296 undergraduate students, lecturers, and administrative staff at the Faculty of Tarbiyah, Universitas KH. Abdul Chalim Mojokerto and analyzed through multiple linear regression in SPSS. The model was statistically significant, F (2, 293) = 201.545, p < .001, and explained 57.6% of the variance in Academic Quality Acceleration. Information Quality was a strong positive predictor (β = .821, p < .001), whereas System Quality did not make a significant unique contribution after their shared variance was considered (β = -.090, p = .090). The findings suggest that users experience academic benefits most clearly when the information delivered by the system is accurate, timely, complete, and accessible. Universities should therefore connect investment in technical infrastructure with sustained improvements in data quality and user evaluation. Because the study was conducted in a single faculty and relied on self-reported perceptions, broader multisite research using objective indicators is needed.